2020
DOI: 10.1002/em.22381
|View full text |Cite
|
Sign up to set email alerts
|

DNA–protein crosslinks from environmental exposure: Mechanisms of formation and repair

Abstract: Many environmental carcinogens cause DNA damage, which can result in mutations and other alterations in genomic DNA if not repaired promptly. Because of the bulkiness of the lesions, DNA–protein crosslinks (DPCs) are one of the types of toxic DNA damage with potentially deleterious consequences. Despite the importance of DPCs, how cells remove these complex DNA adducts has been incompletely understood. However, major progress in the DPC repair field over the past 5 years now supports the view that cells are eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 117 publications
0
17
0
Order By: Relevance
“…When external factors induce DNA damage, the cells can mobilize corresponding repair mechanisms to reverse these damages in order to maintain genetic stability. The nucleotide excision repair (NER) pathway, the major mechanism in the process of DNA repair, primarily eliminates bulky adducts arising from exposure to environmental agents [30][31][32]. Xeroderma pigmentosum group A (XPA) and xeroderma pigmentosum group C (XPC) are the initial recognizing proteins responsible for the recruitment of relevant repair apparatus to the DNA damage [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…When external factors induce DNA damage, the cells can mobilize corresponding repair mechanisms to reverse these damages in order to maintain genetic stability. The nucleotide excision repair (NER) pathway, the major mechanism in the process of DNA repair, primarily eliminates bulky adducts arising from exposure to environmental agents [30][31][32]. Xeroderma pigmentosum group A (XPA) and xeroderma pigmentosum group C (XPC) are the initial recognizing proteins responsible for the recruitment of relevant repair apparatus to the DNA damage [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SPRTN protease activity is tightly regulated by several mechanisms to prevent uncontrolled proteolysis of proteins not at DPC lesions (Kojima and Machida, 2020;Reinking et al, 2020;Stingele et al, 2017). First, SPRTN undergoes the ubiquitin switch (Stingele et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TOP2-DPCs can also be proteolysed by non-proteasomal pathways 245 , 248 , 254 256 , and non-proteolytically by TDP2 following their SUMOylation and unfolding by ZNF451 (refs 257 259 ) (Fig. 6 ).…”
Section: Topoisomerases and Genome Instabilitymentioning
confidence: 99%